Firn Density and Stratigraphy Observations from USGS Benchmark Glaciers ... - Christopher D Stevens; Louis Sass; Caitlyn E Florentine; Christopher J. Mcneil; Emily H Baker; Katherine E Bollen (U.S. Geological Survey, 2023)
This dataset contains observations of snow and firn density and stratigraphy from Site EC on Wolverine Glacier. Site EC is located in the accumulation zone on the northwest flank of the upper glacier at 1350m. Cores were recovered using a FELICS corer to approximately 25m depth at the end of the accumulation season and the end of ablation season starting in 2016. Additional cores were drilled throughout the ablation seasons of 2016 and 2017. The cores were processed in the field. The dataset includes depth-density profiles, ice-lens stratigraphy, and annual-layer depths. Density was calculated by measuring the mass and length of each core section (the corer retrieves cores with uniform diameter, which was measured on randomly selected core sections). Ice lenses were identified by visual inspection. Annual layer depths were determined by identifying dark layers in the core, which are interpreted to be the end-of-melt-season surfaces. ...